Labour union’s website accessibility and information rights fulfilment among workers with disability - Sumartias, Suwandi; Hafiar, Hanny; Amin, Kholidil; Limilia, Putri; Prastowo, Ari Agung (Faculty of Communications Science, Dr. Soetomo University, 2022)
The present study examines website accessibility on the labour union's website regarding their ability to provide a friendly website for people with disabilities. Web Content Accessibility Guidelines (WCAG) were employed to assess web accessibility. Labour union confederation’s website had significant accessibility errors on adaptable, navigable, operable, and low-contrast elements. Besides, the website had severe alerts and errors. Generally, most websites have not employ accessibility guidelines; hence information rights fulfilment among people with disabilities failed to be achieved. The limitation of this research lies in the number of labour union websites being analysed. Nevertheless, this research employs labour confederation websites with many members and federations that represent labour unions based on the type and location in Indonesia. Another limitation lies in the evaluation tools, which are limited to free tools usage. Thus, future research should employ various tools, neither free nor paid tools. Website developers should get socialisation regarding the urgency of website accessibility while repairing some aspects with low scores and errors. The government should enforce accessibility regulations. The community of people with disabilities should actively deliver their feedback to web developers thus their information rights can be fulfilled. The information rights fulfilment among workers with a disability tends to neglect by the labour unions. It can be seen from the labour union confederation's website that it is not accessible yet for all workers, so an inclusive workplace is challenging to achieve.